Tinjauan Yuridis Terhadap Pedagang Kaki Lima Pada Lingkungan UPN Veteran Jakarta Kampus Pondok Labu (International Forum of Researchers and Lecturers, 2023)
Street vendors are the dominant informal economic activity in urban areas. These street vendors are a form of scale economic activity that can produce and or distribute goods and services. Goods sold on roadside and in city centres that are busy with visitors provide necessities for the lower middle class, but it is not uncommon for people from the upper middle class to buy wares from street vendors. The purpose of writing this research is to. This study uses a normative juridical method. The results showed that the street vendors in the UPN Veteran Jakarta environment had filled the sidewalks on the road in front of the UPN Veteran Jakarta campus. Which is where the road or sidewalk should be used by pedestrians so that it is difficult for pedestrians to pass through the road because the road is narrow and there are many vehicles passing by. Thus, it can be concluded that the existence of street vendors, especially those selling in the UPN Veteran Jakarta Campus Pondok Labu environment, clearly violates laws and regulations. This is because the stalls used by street vendors for selling use roads and sidewalks which can disrupt traffic order and deprive pedestrians of their rights. Apart from that, this also damages the beauty of the city's spatial planning which causes the locations where street vendors sell their goods to look shabby and dirty.